Combined transcriptomic and physiological metabolomic analyses elucidate key biological pathways in the response of two sorghum genotypes to salinity stress - Zhang, Fei; Lu, Feng; Wang, Yanqiu; Zhang, Zhipeng; Wang, Jiaxu; Zhang, Kuangye; Wu, Han; Zou, Jianqiu; Duan, Youhou; Ke, Fulai; Zhu, Kai (Frontiers in Plant Science, 2022)
Sorghum is an important food crop with high salt tolerance. Therefore, studying the salt tolerance mechanism of sorghum has great significance for understanding the salt tolerance mechanism of C4 plants. In this study, two sorghum species, LRNK1 (salt-tolerant (ST)) and LR2381 (salt-sensitive (SS)), were treated with 180 mM NaCl salt solution, and their physiological indicators were measured. Transcriptomic and metabolomic analyses were performed by Illumina sequencing and liquid chromatography-mass spectrometry (LC-MS) technology, respectively. The results demonstrated that the plant height, leaf area, and chlorophyll contents in LRNK1 were significantly higher than in LR2381. Functional analysis of differently expressed genes (DEGs) demonstrated that plant hormone signal transduction (GO:0015473), carbohydrate catabolic processes (GO:0016052), and photosynthesis (GO:0015979) were the main pathways to respond to salt stress in sorghum. The genes of the two varieties showed different expression patterns under salt stress conditions. The metabolomic data revealed different profiles of salicylic acid and betaine between LRNK1 and LR2381, which mediated the salt tolerance of sorghum. In conclusion, LRNK1 sorghum responds to salt stress via a variety of biological processes, including energy reserve, the accumulation of salicylic acid and betaine, and improving the activity of salt stress-related pathways. These discoveries provide new insights into the salt tolerance mechanism of sorghum and will contribute to sorghum breeding.